1998
DOI: 10.1111/j.1445-2197.1998.tb04662.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Experience of a Simple Technique for Laparoscopic Chronic Ambulatory Peritoneal Dialysis Catheter Placement

Abstract: Background: Chronic ambulatory peritoneal dialysis (CAPD) is now an established technique for renal dialysis. Patients with renal failure cope poorly with major surgery and it is vital that the dialysis catheter tip is sited accurately in the pelvis if long-term catheter function is to be achieved. Laparoscopic placement of CAPD catheters may have potential advantages for renal patients by avoiding the morbidity of a laparotomy. Methods: A retrospective audit was performed of all CAPD catheters inserted at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 13 publications
3
64
3
Order By: Relevance
“…Prior, smaller, single-center studies comparing laparoscopic and open techniques of PDC placement have, in general, favored the laparoscopic approach with exit site infection rates between 6-23.8 % compared to 8.7-47. 6 % in the open cohort [31][32][33]. Overall, the reported rates of infection from the NSQIP data are lower in comparison with wound-related complications for both LPDC and OPDC; potentially, the infection rates are more pronounced over time as an outpatient as the catheter is used for peritoneal dialysis.…”
Section: Discussioncontrasting
confidence: 45%
“…Prior, smaller, single-center studies comparing laparoscopic and open techniques of PDC placement have, in general, favored the laparoscopic approach with exit site infection rates between 6-23.8 % compared to 8.7-47. 6 % in the open cohort [31][32][33]. Overall, the reported rates of infection from the NSQIP data are lower in comparison with wound-related complications for both LPDC and OPDC; potentially, the infection rates are more pronounced over time as an outpatient as the catheter is used for peritoneal dialysis.…”
Section: Discussioncontrasting
confidence: 45%
“…Among these techniques laparoscopic peritoneal dialysis catheter insertion had been reported to be the method of choice with low visceral injury, bleeding, incisional hernia and catheter disfunction risks. [14,15] On the other hand various meta-analysis have shown that all insertion methods have been comparable and there were no significant differences among different methods. [16][17][18] Currently; laparoscopic insertion of the peritoneal dialysis catheter is prefered due to better evaluation of the intraabdominal region, catheter fixation capability and availability of adhesiolysis upon observation.…”
Section: Discussionmentioning
confidence: 99%
“…Two early retrospective studies comparing laparoscopic and open insertion of PD catheters showed a trend toward lower complications and dysfunction with the laparoscopic group, but did not reach statistical significance [117,118] patients using open insertion with 21 laparoscopic insertions in a randomized prospective trial. They found higher incidence of early fluid leak in the laparoscopic group 9.5 vs. 0 % and no difference in mechanical dysfunction.…”
Section: Open Vs Basic Laparoscopicmentioning
confidence: 99%